Effect of ertugliflozin on glucose control, body weight, blood pressure and bone density in type 2 diabetes mellitus inadequately controlled on metformin monotherapy (VERTIS MET). Issue 3 (2nd October 2017) - Rosenstock, Julio; Frias, Juan; Páll, Dénes; Charbonnel, Bernard; Pascu, Raluca; Saur, Didier; Darekar, Amanda; Huyck, Susan; Shi, Harry; Lauring, Brett; Terra, Steven G.
Abstract : Aim: We evaluated the efficacy and safety of ertugliflozin, an SGLT2 inhibitor, in type 2 diabetes mellitus (T2DM) inadequately controlled (HbA1c, 7.0%‐10.5%) with metformin monotherapy (≥1500 mg/d for ≥8 weeks). Methods: This was a double‐blind, 26‐week, multicentre study with ongoing 78‐week extension (ClinicalTrials.gov identifier: NCT02033889). A total of 621 participants were randomized 1:1:1 to placebo, or ertugliflozin 5 or 15 mg/d. The primary endpoint was change from baseline at week 26 in HbA1c. Secondary efficacy endpoints were change from baseline at week 26 in fasting plasma glucose (FPG), body weight, systolic/diastolic blood pressure (SBP/DBP) and number of participants with HbA1c <7.0% (53 mmol/mol). Pre‐specified adverse events (AEs) of special interest and percent change from baseline in bone mineral density (BMD) were also assessed at week 26. Results: At week 26, the placebo‐adjusted least‐squares mean change from baseline HbA1c (8.1%) was −0.7% and −0.9% for ertugliflozin 5 and 15 mg, respectively (both P  < .001), to final means of 7.3% and 7.2%, respectively. The odds of HbA1c <7.0% were significantly greater in both ertugliflozin groups vs placebo. Ertugliflozin significantly reduced FPG, body weight, SBP and DBP vs placebo. The incidence of genital mycotic infections was higher in the ertugliflozin groups (female subjects: placebo, 0.9%; ertugliflozin 5 mg, 5.5%; ertugliflozin 15 mg, 6.3% [ P  = .032]; male subjects: 0%; 3.1%; 3.2%, respectively), as was the incidence of urinary tract infections and symptomatic hypoglycaemia. The incidence of hypovolaemia AEs was similar across groups. Ertugliflozin had no adverse impact on BMD at week 26. Conclusions: Ertugliflozin added to metformin in patients with inadequately controlled T2DM improved glycaemic control, reduced body weight and BP, but increased the incidence of genital mycotic infections.